From Raynaud Phenomenon to Systemic Sclerosis in COVID-19: A Case Report. (February 2022) - Giuggioli, Dilia; Spinella, Amelia; de Pinto, Marco; Mascia, Maria Teresa; Salvarani, Carlo
Abstract : ABSTRACT: In 2019, the novel SARS-CoV-2 infection emerged, causing the disease called COVID-19, which primarily affects the respiratory tract and lung at alveolar and interstitial levels. Systemic sclerosis (SSc) is an autoimmune connective disease characterized by vascular abnormalities and diffuse and progressive fibrosis of the skin and internal organs. Raynaud phenomenon (RP) occurs in virtually all patients affected by SSc and, in most cases, is an onset symptom of the disease; that is, RP may appear several years before overt illness. Although the exact pathophysiologic pathways leading to RP and SSc are still unknown, several infectious agents, especially viruses, have been suggested as possible triggering factors. Here, the authors describe the first case of RP secondary to SSc following SARS-CoV-2 infection.